«Նախիջևանի միջանցքի» գործարկման վերաբերյալ Իրանի և Ադրբեջանի ակնկալիքները - Իսրայելյան, Արմեն (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Taking geopolitical situation after the 44-day war in 2020, Azerbaijan put the issue of the so-called "Zangezur corridor" on the agenda. Baku is trying to achieve two strategic goals: to close the land connection between Armenia and Iran and to get out of Iran's dependence on the Nakhijevan issue. However, Azerbaijan, faced with the opposition of Armenia and Iran, changed its strategy. In parallel with its aggressive policy against Armenia, Baku began negotiations with Tehran on the construction of a new route connecting Nakhijevan through Iranian territory. In parallel with the aggressive policy of Azerbaijan in the issue of the so-called "Zangezur corridor" Baku for the first time since March 2021 began to consider the territory of Iran as an alternative way of establishing communication with Nakhichevan. In March 2022, Hikmet Hajiyev, Head of the Foreign Relations Department of the President of Azerbaijan and Assistant to the President, in an interview with Turkish media during the "Antalya Diplomatic Forum" held in Turkey, first stated Baku's intention to connect Nakhichevan through the territory of Iran. A few months after Hajiyev's statement, Ramil Usubov, secretary of the Azerbaijani Security Council, and Jeyhun Bayramov, Azerbaijani Foreign Minister, also proclaimed Baku's aims to link Nakhichevan through the territory of Iran. By manipulating the issue of the "Nakhijevan corridor," Azerbaijan is trying to divert the attention of countries that are interested in preserving the territorial integrity of Armenia from its initiatives to forcibly open the so-called "Zangezur corridor. On the other hand, by implementing joint projects with Iran, Azerbaijan is trying to stress its role in relations with the West and Israel, expecting political and financial support from these important actors in exchange for refusing to participate in these projects.
Keywords: Միջազգային հարաբերություններ; Իրան; Ադրբեջան; Հայաստան